2020
DOI: 10.1111/opo.12748
|View full text |Cite
|
Sign up to set email alerts
|

Impaired visual acuity caused by uncorrected refractive errors and amblyopia in a German paediatric cohort

Abstract: Purpose This study describes the prevalence of visual impairment caused by uncorrected distance refractive error and the spectacle coverage in a large cohort of German children and adolescents. Furthermore, we determined the prevalence of amblyopia and amblyopia treatment. Methods Optometrists carried out visual acuity (VA) testing, non‐cycloplegic autorefraction, VA retesting with the refractive correction obtained by autorefraction, and if necessary subjective refraction and cover‐test in 1,874 subjects (901… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…With regards to the high incidence rate of myopia in children in WPRO, we believe that the role of environment factors is more important than genetic and ethnic factors. The Refractive Error Study in Children (RESC) reported that the prevalence of myopia was higher in China, compared to Nepal, Chile, India, South Africa, and Malaysia consistent with other reports of high myopia rates among children of east [57,[75][76][77][78][79][80][81]. There might be three major factors for myopia formation and development by previous reports: the first is the excessive intensity of near vision work related to the pressure of more rigorous education system.…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation
“…With regards to the high incidence rate of myopia in children in WPRO, we believe that the role of environment factors is more important than genetic and ethnic factors. The Refractive Error Study in Children (RESC) reported that the prevalence of myopia was higher in China, compared to Nepal, Chile, India, South Africa, and Malaysia consistent with other reports of high myopia rates among children of east [57,[75][76][77][78][79][80][81]. There might be three major factors for myopia formation and development by previous reports: the first is the excessive intensity of near vision work related to the pressure of more rigorous education system.…”
Section: Plos Onesupporting
confidence: 83%
“…Further, we grouped fourteen studies from SEARO [51][52][53][54][55][56][57][58][59][60][61][62][63][64], and the pooled prevalence was 2.26 (95% CI: 0.85~6.01) [ Fig 8]. The heterogeneity of the estimates from the included studies was very high.…”
Section: Forest Plot Showing Prevalence Of Ure Among Gbd Sub-regions ...mentioning
confidence: 99%
“…Previous studies have shown a prevalence of vision impairment among school children in Nigeria ranging from 1.2 to 6.9% 3 5 . Many conditions are known to cause vision impairment in children 6 , the leading cause identified as uncorrected refractive errors and amblyopia 6 – 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In amblyopia, the visual stimulus that enters the eye is not sufficiently clear, thus resulting in a below-normal best-corrected visual acuity (BCVA) in one or both eyes, with no organic eye lesion ( 1 ). The prevalence rates of amblyopia in children vary from 1 to 5% ( 2 , 3 ). To date, some studies have pointed out that there are pathological changes in the morphology and function of the visual pathway and visual center in amblyopic patients.…”
Section: Introductionmentioning
confidence: 99%